An autophagy-related long non-coding RNA prognostic model and related immune research for female breast cancer - Chen, Jiafeng; Li, Xinrong; Yan, Shuixin; Li, Jiadi; Zhou, Yuxin; Wu, Minhua; Ding, Jinhua; Yang, Jiahui; Yuan, Yijie; Zhu, Ye; Wu, Weizhu (Frontiers in Oncology, 2022)
It was widely accepted that autophagy and tumor immune microenvironment play an important role in the biological process of breast cancer (BRCA). And long non-coding RNAs(lncRNAs), as vital regulatory molecules, are also involved in the process of occurrence and development of BRCA. In this study, 10 autophagy-related lncRNAs(ARlncRNAs) were identified to construct prognostic model through univariate and multivariate Cox analysis, and the prognosis of BRCA was negatively correlated with the risk score. The ARlncRNAs model was proved to be a reliable independent prognostic factor for BRCA. In addition, Gene Set Enrichment Analysis(GSEA) enrichment analysis suggested that several tumor-related pathways were enriched in the high-risk group, while several immune-related pathways were enriched in the low-risk group. Patients in the low-risk group had higher immune scores and were more active in immune cells and immune pathways. Patients in the low-risk group had higher PD-1 and CTLA-4 expression levels, and received more benefits from Immune checkpoint inhibitors(ICIs) treatment. In conclusion, The ARlncRNAs model can well predict the prognosis of patients with BRCA and is of great significance to guide the individualized treatment of these patients.